MEaSUREs ITS_LIVE Sentinel-1 Image-Pair Glacier and Ice Sheet Surface Velocities: Version 2 (Greenland Sample Products) - Lei, Yang; Gardner, Alex; Piyush Agram (Zenodo, 2021)
We provide 21 sample products of MEaSUREs ITS_LIVE Sentinel-1 Image-Pair Glacier and Ice Sheet Surface Velocities: Version 2 in three test regions of Greenland Ice Sheet. The full archive of version 2 ITS_LIVE products (including image pair maps, data cubes and mosaics) from Sentinel-1 as well as other optical sensors (Landsat-4/5/6/7/8 and Sentinel-2) can be found at the ITS_LIVE project website: https://its-live.jpl.nasa.gov. Sensor : Sentinel-1A/B Processor : ISCEv2.4.1 (topsApp -> Geogridv1.4.0 -> autoRIFTv1.4.0) Project : NASA MEaSUREs project ITS_LIVE Region 1 (69.13N, 50.88W; Jakobshavn Isbræ Glacier): 7 ascending image pairs Region 2 (77.61N, 42.79W; central north of interior Greenland): 3 ascending image pairs Region 3 (72.48N, 35.87W; central south of interior Greenland): 10 descending image pairs and 1 ascending image pair This serves as a supplementary dataset for the companion journal article submitted to Earth System Science Data (to appear). Acknowledgement : This effort was funded by the NASA MEaSUREs program in contribution to the Inter-mission Time Series of Land Ice Velocity and Elevation (ITS_LIVE) project (https://its-live.jpl.nasa.gov/) and through Alex Gardner’s participation in the NASA NISAR Science Team.